Perilaku Pengurangan Sampah: Potensi Pengungkapan dan Pelaporan Keberlanjutan di Perguruan Tinggi - Wicaksono, Aditya Pandu; Mahfuroh, Riana; Bagus, Arya Lintang Risang (Universitas Pendidikan Ganesha, 2020)
Not only does accounting focus on financial aspect, but also placing attention on non-financial aspect such as sustainability issue that covers management of waste. Higher education institutions are required to take an active role in order to mitigate waste production although there is no regulation and guidance on sustainability. This research is conducted to discover predictor variables that influence waste reduction behavior in higher education. Samples are 185 accounting undergraduate students in Universitas Islam Indonesia. The questionnaire is electronically distributed. Data are analyzed using statistic tool namely smart PLS version 3.0. This research finds there are no significant influences from TPB’s independent variables to intention. Convenience and knowledge do not significantly influence intention reducing waste production. On the other hand, moral obligation is the only independent variable that significantly influences intention. Intention, additionally, is significant predictor for performing waste reduction behavior.